Characterization of Four Medically Important Toxins from Centruroides huichol Scorpion Venom and Its Neutralization by a Single Recombinant Antibody Fragment - Hugo Valencia-Martínez; Timoteo Olamendi-Portugal; Rita Restano-Cassulini; Hugo Serrano-Posada; Fernando Zamudio; Lourival D. Possani; Lidia Riaño-Umbarila; Baltazar Becerril (Toxins, 2022)
Centruroides huichol scorpion venom is lethal to mammals. Analysis of the venom allowed the characterization of four lethal toxins named Chui2, Chui3, Chui4, and Chui5. scFv 10FG2 recognized well all toxins except Chui5 toxin, therefore a partial neutralization of the venom was observed. Thus, scFv 10FG2 was subjected to three processes of directed evolution and phage display against Chui5 toxin until obtaining scFv HV. Interaction kinetic constants of these scFvs with the toxins were determined by surface plasmon resonance (SPR) as well as thermodynamic parameters of scFv variants bound to Chui5. In silico models allowed to analyze the molecular interactions that favor the increase in affinity. In a rescue trial, scFv HV protected 100% of the mice injected with three lethal doses 50 (LD50) of venom. Moreover, in mix-type neutralization assays, a combination of scFvs HV and 10FG2 protected 100% of mice injected with 5 LD50 of venom with moderate signs of intoxication. The ability of scFv HV to neutralize different toxins is a significant achievement, considering the diversity of the species of Mexican venomous scorpions, so this scFv is a candidate to be part of a recombinant anti-venom against scorpion stings in Mexico.